Hungarian and European Conscious Ageing Network: Cooperation between Municipalities, Municipality Associations, NGOs and business to promote Active and Conscious Ageing in Hungary and Europe - Kinga (Magyar Gerontológia, 2025)
As the European population is ageing, local communities are increasingly confronted with complex, interconnected challenges. Demographic change intersects with economic uncertainty, social fragmentation, health inequalities, labour market restructuring and the broader polycrisis affecting Europe.